Antropologías periféricas. Una mirada a la construcción de la antropología en Colombia (2010)
ABSTRACT: This paper is a reflection on the history and future of anthropology in Colombia. Our intention is to discuss certain aspects which seem to be indicative, in one hand, of the singularity of the exercise of this discipline in Colombia and, in the other hand, of the transverse dynamics of asymmetric relations between the hegemonic anthropologies of the Northern Atlantic countries and the Southern subaltern ones. The analysis emphasizes the dissidences as different ways of doing anthropology, questioning the discipline’s orthodoxy, offering interesting ligths for its holistic understanding. This paper also addresses the issue of nowdays anthropology, showing the impact of neoliberal policies in the increasingly technocratic perspective that the discipline assumes in its conformation and practice.